Acute Ataxia in Children - A Series of Cases to Emphasize the Clinical Approach - Maria Weimer; Robin English (Association of American Medical Colleges, 2011)
Abstract Introduction This module was developed to help medical students, residents, and fellows learn how to approach the evaluation of children with acute ataxia. While discussing these cases with students and residents, it became apparent that learners often were unable to specifically elicit the information (history and examination) they sought in thinking through ataxia. Obtaining a thorough and accurate history is one of the most important skills a clinician can possess, and the ability to do that with pediatric patients is often extremely challenging. Therefore, each of these cases offers teaching points highlighting particular aspects of the history or physical examination that requires specificity. Methods The cases are intended to be discussed in a small-group format with a knowledgeable and prepared facilitator, although the facilitator need not be an expert in the field of pediatric neurology. In addition, role play opportunities are included for some cases so that learners can also improve their skills in communicating with families. Results The primary author has discussed these cases informally for several years. However, in the interest of receiving more formal feedback, an evaluation form was developed. The form lists several positive statements for each case, accompanied by a 5-point Likert scale. To date, this form has been completed for 48 case discussions, and the average score is 4.84 out of possible 5 points. Discussion While there are limitations to this type of evaluative process, we believe that this response demonstrates that learners feel it helps them to develop clinical skills. In addition to getting feedback from students on the effectiveness of the cases, the second author (a pediatric hospitalist) discussed the cases with members of her team as well. The reason for this was to examine whether the cases were easily discussed by a facilitator not intimately familiar with the patients themselves. Overall, she found the cases to have sufficient detail but some minor adjustments were made, and feedback from students in her groups was similar to that received by the neurologist's groups.